(3cJGH ehGRjf GdCYeGds
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdefaQO HGdhMOGfjI hGdcHQjGA hGdYXeI s
(3BNQgG (B:s
(3hcGfJ GdaVjdI ai UjGeg Ydi TgQ QLH fGWbI hGdMeO ddg hMOg s
(3GdejcQhajde eXde LOkGs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJUha hGdBOGH GdTQYjIs